2022
DOI: 10.1161/jaha.122.027538
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Extracellular Signal‐Regulated Kinase/Thromboxane A2/Prostanoid Receptor Pathway Aggravates Endothelial Dysfunction and Insulin Resistance in a Mouse Model of Metabolic Syndrome

Abstract: Background Metabolic syndrome is characterized by insulin resistance, which impairs intracellular signaling pathways and endothelial NO bioactivity, leading to cardiovascular complications. Extracellular signal‐regulated kinase (ERK) is a major component of insulin signaling cascades that can be activated by many vasoactive peptides, hormones, and cytokines that are elevated in metabolic syndrome. The aim of this study was to clarify the role of endothelial ERK2 in vivo on NO bioactivity and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…MAPK1 assumes a crucial role in the regulation of diabetes and inflammation ( Ge et al, 2020 ). In mouse models of metabolic syndrome, ERK2 overexpression increased insulin resistance ( Sato et al, 2022 ), while endothelial ERK2 deletion improved insulin resistance ( Kujiraoka et al, 2022 ). Our results suggest that GRh3 may alleviate insulin resistance by downregulating MAPK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK1 assumes a crucial role in the regulation of diabetes and inflammation ( Ge et al, 2020 ). In mouse models of metabolic syndrome, ERK2 overexpression increased insulin resistance ( Sato et al, 2022 ), while endothelial ERK2 deletion improved insulin resistance ( Kujiraoka et al, 2022 ). Our results suggest that GRh3 may alleviate insulin resistance by downregulating MAPK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the pathophysiology of Mets, a rodent model fed a high-fat and high-sucrose diet (HFHSD) has been used [ 2 , 3 , 4 , 5 ]. The contribution of HFHSD to insulin resistance depends on the strains of mice, and C57BL/6 mice were demonstrated to develop insulin resistance by HFHSD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high‐affinity receptor activated by TXA 2 is called the TXA 2 receptor (TP receptor), a G‐protein coupled receptor located on the cell membrane, which is widely expressed in the thymus, spleen and liver (Nakahata, 2008). TP receptors have been reported to be activated in atherosclerosis and inflammation and play a critical role in endothelial dysfunction and insulin resistance (Eckenstaler et al, 2022; Sato et al, 2022). Our previous research has demonstrated that TXA 2 was elevated in obesity and that the TXA 2 –TP receptor axis promoted adipose tissue macrophage M1 polarization, leading to insulin resistance and facilitated excessive hepatic gluconeogenesis in the liver (Y. Dai et al, 2023; Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%